2017
DOI: 10.1371/journal.pone.0176108
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-specific phospholipase C inhibition down- regulates CXCR4 expression and interferes with proliferation, invasion and glycolysis in glioma cells

Abstract: BackgroundThe chemokine receptor CXCR4 plays a crucial role in tumors, including glioblastoma multiforme (GBM), the most aggressive glioma.Phosphatidylcholine-specific phospholipase C (PC-PLC), a catabolic enzyme of PC metabolism, is involved in several aspects of cancer biology and its inhibition down-modulates the expression of growth factor membrane receptors interfering with their signaling pathways.In the present work we investigated the possible interplay between CXCR4 and PC-PLC in GBM cells.MethodsConf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
3
18
0
1
Order By: Relevance
“…Agents affecting HER2 expression and mechanisms of HER2 endocytosis and recycling may therefore have profound effects on HER2-driven oncogenic signaling transduction [ 12 ]. Although detailed investigations on the effects of D609 on HER2-driven oncogenic signaling pathways were out of the scope of the present study, our Western blot experiments confirmed high levels of constitutive Akt phosphorylation in untreated SKOV3.ip cells, and showed decreases in the levels of pAKT and mTOR in cells exposed to D609 for 24 h. Interestingly, we recently reported that PC-PLC inhibition by D609 also induced downmodulation of the CXCR4 receptor in U87MG glioma cells, an effect which was similarly associated with remarkable decreases in AKT phosphorylation and reduced cell proliferation [ 35 ]. The MAPK phosphorylation levels were instead maintained rather high in D609-treated SKOV3.ip cells (84 ± 3% versus untreated controls at 24–72 h), likely due to the reported constitutive Ras activation present in these cells [ 30 ].…”
Section: Discussionsupporting
confidence: 66%
“…Agents affecting HER2 expression and mechanisms of HER2 endocytosis and recycling may therefore have profound effects on HER2-driven oncogenic signaling transduction [ 12 ]. Although detailed investigations on the effects of D609 on HER2-driven oncogenic signaling pathways were out of the scope of the present study, our Western blot experiments confirmed high levels of constitutive Akt phosphorylation in untreated SKOV3.ip cells, and showed decreases in the levels of pAKT and mTOR in cells exposed to D609 for 24 h. Interestingly, we recently reported that PC-PLC inhibition by D609 also induced downmodulation of the CXCR4 receptor in U87MG glioma cells, an effect which was similarly associated with remarkable decreases in AKT phosphorylation and reduced cell proliferation [ 35 ]. The MAPK phosphorylation levels were instead maintained rather high in D609-treated SKOV3.ip cells (84 ± 3% versus untreated controls at 24–72 h), likely due to the reported constitutive Ras activation present in these cells [ 30 ].…”
Section: Discussionsupporting
confidence: 66%
“…Numerous studies suggest that the overexpression of CXCR4 facilitates proliferation, angiogenesis, invasion, and metastasis, as well as chemotherapy and radiotherapy resistance of glioma in several glioma cell lines and mouse models [ 16 21 ]. Administration of either CXCR4 neutralizing antibody or CXCR4 siRNA impairs the enhanced glioma malignancy (proliferation, angiogenesis, invasion, metastasis, and postchemotherapy and postradiotherapy recurrence) and increases median survival in vivo glioma models [ 17 20 , 22 27 ]. Thus, the potential of CXCR4 as an antitumor target has been a popular research topic.…”
Section: Introductionmentioning
confidence: 99%
“…As delivery carriers of PTX, their morphology has significant influences on drug entrapment and release behaviors, which further affects antitumor activity (Wang et al., 2015 ). Furthermore, the disruption of programed cell proliferation signaling pathways may result in elevated cell death, so the changes of molecule biology in glioma cells play important roles in malignant glioma treatment (Mercurio et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%